Characterization of blast resistance related protein domains in wheat for molecular marker development: Wheat blast resistance protein domain (Journal of the Bangladesh Agricultural University, 2019)
Wheat blast is a devastating disease which is baffling scientists from its inception. This study characterized the blast resistance related protein domains with a view to develop molecular markers to identify resistant wheat genotypes against Blast fungus Magnaporthe oryzae. A genome browse analysis detected that the candidate resistance gene against blast could be located in several different chromosomes. An in silico analysis was collected with fifty nucleotide-binding site leucine-rich repeat (NBS-LRR), leucine-rich repeat (LRR), pathogenesis and resistance protein-encoding accessions on the basis of the previous resistance report. The phylogenetic tree of those putative resistance accessions, bearing resistance related protein-encoding domains, showed that an NBS-LRR accession JP957107.1 has 67% similarity with the disease resistance protein domain encoding accession of Brazilian resistant cultivar Thatcher. By contrast, the rice blast resistance Pita gene has 72% similarity with 18 pathogenesis protein domain encoding accessions. Among putative protein domains, disease resistance protein of Thatcher has 78% similarity with two NBS-LRR protein domains AAZ99757.1 and AAZ99757.1. Eighteen microsatellite markers were designed from eighteen putative NBS-LRR protein encoding accessions along with Piz3 marker. The 19 markers were unable to separate resistant and susceptible genotypes. Diffused versus conspicuous bands indicated either presence of insertion/deletion (InDel) or single nucleotide polymorphism (SNP) among wheat genotypes. Detection of InDel or SNP markers is a subject of further investigation. Additional markers are needed to be designed using new NBS-LRR, pathogenesis, coiled-coil (CC), translocated intimin receptor (TIR) resistance protein encoding accessions to find out markers specific for blast resistance.J. Bangladesh Agril. Univ. 17(2): 161–171, June 2019